Method for synthesizing the concept of automating the system to manage personnel training processes based on categorial analysis - Nykyforov, Alexey; Nykyforov, Anton; Antoshchenkov, Roman; Polyansky, Pavlo; Halych, Ivan; Kis, Victor; Dombrovska, Alla; Kilimnik, Inna; Usyk, Andrii (Eastern-European Journal of Enterprise Technologies, 2024)
This paper considers a three-level system for managing personnel training within the Ministry of Defense of Ukraine. When devising the concept of automating control processes in systems of this kind, the key issue is to ensure completeness in significant aspects of the management process. Insufficient conceptual completeness compromises effectiveness of the automated system for organizational control (ASOC) and causes difficulties (impossibility) in its further modernization. A method has been proposed for formulating functional tasks (FTs) in specialized software (SSW) for ASOC based on categorical analysis in combination with the provisions of the conceptual design of automated control systems (ACS). The application of this method was demonstrated using an example of the system for managing personnel training. Categorical analysis of the management process was carried out for the strategic, operational, and tactical hierarchical levels of the system based on three dual pairs. Eight control aspects were obtained. On their basis, 79 FTs were stated for the strategic level. For the operational and tactical levels, by taking into account the specificity of training, the number of aspects was 2; FTs ‒ 204 and 195, respectively. An example has been given for two of the eight aspects of control, their interpretation and formulation of FTs for the strategic level of management. The generated FTs represent the concept of ASOC and provide, within the established boundaries of analysis, the completeness of control aspects in personnel training. The reported results are of interest in the conceptual design of large ASOC, as well as in the formation of technical specifications for software developers